Pro ASP.NET 4 in VB 2010 3rd Edition - MacDonald, Matthew (Apress, 2012)
In this book, you’ll learn everything you need to master ASP.NET 4. If you’ve programmed with a previous version of ASP.NET, you can focus on new features such as ASP.NET MVC (Chapter 32), ASP.NET Dynamic Data (Chapter 33), and Silverlight (Chapter 34). If you’ve never programmed with ASP.NET, you’ll find that this book provides a well-paced tour that leads you through all the fundamentals, along with a backstage pass that lets you see how the ASP.NET internals really work. The only requirement for this book is that you have a solid understanding of the VB language and the basics of .NET. If you’re a seasoned Java or C++ developer but you’re new to VB, you may find it easier to start with a book about .NET fundamentals, such as Pro VB 2010 and the .NET 4.0 Platform by Andrew Troelsen (Apress, 2010).